PMD in high-bit-rate transmission and means for its mitigation - Noé, Reinhold; Sandel, D; Mirvoda, V (IEEE JOURNAL OF SELECTED TOPICS IN QUANTUM ELECTRONICS)

Strategies for fast control speed and DC drift avoidance in distributed LiNbO3-based PMD compensators - Noé, Reinhold; Sandel, D (IEEE PHOTONICS TECHNOLOGY LETTERS)

Design of a tunable optical chromatic dispersion compensator with simplified control of a Mach-Zehnder lattice, and dispersion slope mitigation - Noé, Reinhold; Gao, Z (ELECTRICAL ENGINEERING)

Non-magnetic 30 dB integrated optical isolator in III/V material - Ibrahim, SK; Bhandare, S; Sandel, D; Zhang, H; Noé, Reinhold (ELECTRONICS LETTERS)

Positivity of Dunkl's intertwining operator via the trigonometric setting - Rösler, Margit; Voit, Michael (International Mathematics Research Notices)
In this note, a new proof for the positivity of Dunkl's intertwining operator in the crystallographic case is given. It is based on an asymptotic relationship between the Opdam-Cherednik kernel and the Dunkl kernel as recently observed by M. de Jeu, and on positivity results of S. Sahi for the Heckman-Opdam polynomials and their non-symmetric counterparts.

An adaptive channel tracking method for MIMO-OFDM systems - Tong, Jun; Gong, Yaohuan; Sun, Shengxian (Int.\ Conf.\ Comm.\ Circuits Syst.)
The tracking of the time-varying channel is crucial for MIMO-OFDM wireless communication systems. Aiming at doubly-selective fading MIMO channels, we present a novel pilot pattern and the corresponding adaptive channel tracking algorithm. Compared with the traditional pilot patterns, the new pattern has higher frequency efficiency and is more suitable for large transmit arrays. The computational complexity, frequency efficiency and BER performance of the system assisted by the proposed channel tracking scheme are analyzed. Simulation results demonstrate that the proposed scheme can track the timevarying channel effectively.

Polyspectra of analytic signals - Schreier, Peter J.; Scharf, Louis L. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
For complex signals, n-th order moment functions can be defined in 2n different ways, depending on the placement of complex conjugates. We demonstrate that, for stationary analytic signals, only a few of these different moments are actually required for a complete n-th order description. Which, and how many of them, depends on the signal’s spectrum. We investigate properties of n-th order moments and spectra with different conjugation patterns and show how they provide different information about the signal.

Ätztechnik - Hilleringmann, Ulrich (Silizium-Halbleitertechnologie)
In der Halbleitertechnologie werden die Materialien Siliziumdioxid, Siliziumnitrid, Polysilizium, Silizium, Aluminium sowie Wolfram und Titan mit ihren jeweiligen Metallsiliziden geätzt. Die Ätztechnik dient dabei zum ganzflächigen Abtragen eines Materials oder zum Übertragen der Struktur des lithografisch erzeugten Lackmusters in die darunter liegende Schicht. Für diese Aufgabe bieten sich einerseits nasschemische Ätzlösungen an, zum anderen eignen sich speziell entwickelte Trockenätzverfahren zur geforderten präzisen Strukturübertragung vom Lack in das Material.

Imprint structured organic thin film transistors as driving circuit in single-use sensor applications - Hilleringmann, Ulrich; Pannemann, C. (Fifth International Symposium on Instrumentation and Control Technology)

Piezoresistive pressure sensors in CVD diamond for high-temperature applications - Otterbach, Ralf; Hilleringmann, Ulrich (Fifth International Symposium on Instrumentation and Control Technology)

Coherent sheaves on rational curves with simple double points and transversal intersections - Burban, Igor; Drozd, Yu. (Duke Mathematical Journal)

Indecomposables of the derived categories of certain associative algebras - Burban, Igor; Drozd, Yu. (Proceedings of the ICRA-X Conference, Toronto 2002)

Derived categories of coherent sheaves on rational singular curves - Burban, Igor (Representations of finite dimensional algebras and related topics in Lie theory and geometry)

Derived tameness of nodal algebras - Burban, Igor; Drozd, Yu. (J. Algebra)

Increased electrical yield via water flow over the front of photovoltaic panels - Krauter, Stefan (Solar Energy Materials & Solar Cells)

Lie groups of germs of analytic mappings - Glöckner, Helge (Infinite dimensional groups and manifolds. Based on the 70th meeting of theoretical physicists and mathematicians at IRMA, Strasbourg, France, May 2004.)
Keywords: 22E65; 22E67; 46H05; 46T25

Lie groups over non-discrete topological fields - Glöckner, Helge

Differential calculus over general base fields and rings. - Bertram, W.; Glöckner, Helge; Neeb, K.-H. (Expositiones Mathematicae)
Keywords: 58C20; 22E65; 26E15; 26E20; 26E30

Tensor products in the category of topological vector spaces are not associative. - Glöckner, Helge (Commentationes Mathematicae Universitatis Carolinae)
Keywords: 46A32; 46A16; 22A05

Examples of differentiable mappings into non-locally convex spaces. - Glöckner, Helge (Topology Proceedings)
Keywords: 58C20; 46G05; 26E20; 46A16; 46G20